"F(s)=L(y)=\\int\\limits_0^\\infty e^{-s\\cdot t}y(t)\\,dt\\\\\nL(y'')=\\int\\limits_0^\\infty e^{-s\\cdot t}y''(t)\\,dt=0-y'(0)\\cdot 1+s\\cdot\\int\\limits_0^\\infty e^{-s\\cdot t}y'(t)\\,dt=\\\\\n=-5+s\\cdot (0-y(0)\\cdot 1+s\\cdot \\int\\limits_0^\\infty e^{-s\\cdot t}y(t)\\,dt)=\\\\\n= -5-3\\cdot s+s^2\\cdot F(s).\\\\\n\n\\int\\limits_0^\\infty e^{-s\\cdot t}f(t)\\,dt=\\int\\limits_0^\\pi e^{-s\\cdot t}f(t)\\,dt+\\int\\limits_\\pi^\\infty e^{-s\\cdot t}f(t)\\,dt=\\\\=\\int\\limits_0^\\pi e^{-s\\cdot t}\\cdot 1\\,dt+0=\\frac{1-e^{-\\pi s}}{s}.\\\\\n\n -5-3\\cdot s+s^2\\cdot F(s)+16\\cdot F(s)=\\frac{1-e^{-\\pi s}}{s}\\\\\n(s^2+16)F(s)=5+3\\cdot s+\\frac{1-e^{-\\pi s}}{s}=\\frac{5s+3s^2+1-e^{-\\pi s}}{s}\\\\\nF(s)=\\frac{5s+3s^2+1-e^{-\\pi s}}{s(s^2+16)};"
Comments
Leave a comment